2017
DOI: 10.1094/pdis-07-16-1002-re
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Disease Induced by Three Strains of Tobacco etch virus in Capsicum annuum L.

Abstract: Tobacco etch virus (TEV; genus Potyvirus) strains HAT, Mex21, and N were evaluated comparatively for their pathogenicity and effects on growth of Capsicum annuum L. ‘Calwonder’. Each TEV strain induced an initial systemic symptom of vein-clearing but subsequent disease symptoms ranged from mild (HAT) to moderate (Mex21) to severe (N). Effects on plant growth parameters closely reflected disease symptoms induced by each TEV strain. HAT-infected Calwonder plants did not differ from the healthy control for plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…All plants inoculated by each TEV strain (HAT, Mex21, and N) became infected, and their respective type of symptom development occurred as described previously [ 13 ]. Systemic vein-clearing developed for all virus-inoculated plants (for each of the three TEV strains) by 7 dpi.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All plants inoculated by each TEV strain (HAT, Mex21, and N) became infected, and their respective type of symptom development occurred as described previously [ 13 ]. Systemic vein-clearing developed for all virus-inoculated plants (for each of the three TEV strains) by 7 dpi.…”
Section: Resultsmentioning
confidence: 99%
“…and Capsicum annuum (bell pepper). In each of the different plant species, HAT induced mild disease symptoms, Mex21 moderate disease symptoms and N severe disease symptoms [ 12 , 13 ]. In bell pepper plants, symptom severity correlated with impacts on plant height and weight; however, accumulation of virus in systemically infected leaves was greater for HAT- than N-infected plants at 10 dpi and similar at 20, 30 and 40 dpi, despite the differences in impact on plant growth and development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that these values were significantly lower for CMV+PepMoV mixed infection when compared to species infected with a single virus. On the other hand, Murphy & Morawo (2017) reported that above ground fresh weight of TEV-strain Mex21 infected pepper plants was significantly less than for the healthy control. Al-Saleh et al ( 2007) was evaluated selected peanut cultivars for reaction to TSWV in field plots in 2001, 2002, and 2003.…”
Section: Fresh and Dry Weight Of Green Partsmentioning
confidence: 94%
“…Yield reduction due to TEV can reach up to 70% (Koenning & McClure 1981). Murphy & Morawo (2017) evaluated TEV strains HAT, Mex21, and N for their pathogenicity and effects on growth of 'Calwonder' pepper. Effects on plant growth parameters closely reflected disease symptoms induced by each TEV strain.…”
Section: Introductionmentioning
confidence: 99%